(NiFe)S2 nanoparticles grown on graphene as an efficient electrocatalyst for oxygen evolution reaction. (1st October 2018) - Liu, Chenyu; Ma, Hui; Yuan, Mengwei; Yu, Zihuan; Li, Jian; Shi, Keren; Liang, Zupei; Yang, Yan; Zhu, Tianjiao; Sun, Genban; Li, Huifeng; Ma, Shulan
Abstract: High-performance and cost-effective electrocatalysts are vital for oxygen evolution reaction (OER) during water splitting process. Herein, we demonstrate the first report on the facile synthesis of (NiFe)S2 nanoparticles grown on graphene ( abbr. (NiFe)S2 -GN, where GN stands for graphene), through a simple sulfidation process of the NiFe LDH-GO composites (GO is graphene oxide). Characterization of the as-prepared (NiFe)S2 -GN is carried out in details by XRD, FESEM, TEM and HRTEM, XPS, and Raman spectra. Under 400 °C, the NiFe LDH nanosheets decorated on GO surface react with sulfur and transform into (NiFe)S2 nanoparticles with the size of 30–50 nm, simultaneously, GO is reduced to GN, forming the (NiFe)S2 -GN nanocomposites. By changing the concentrations of the added salts, various (NiFe)S2 -GN- x composites ( x is the starting salt concentrations such as 0.16, 0.2 and 0.40 M added into GO suspension) are obtained. The (NiFe)S2 in (NiFe)S2 -GN is formed as a single phase by crystal lattice doping of Ni and Fe, showing an exact composition of (Ni0.75 Fe0.25 )S2 . Among the composites, the (NiFe)S2 -GN-0.2 exhibits optimized electrocatalytic activity. It presents superior OER performance with an overpotential of 320 mV to achieve a current density of 10 mA cm −2 in 1 M KOH, and the Tafel slope of 61 mV/dec is smaller than that (68 mV/dec) of the commercial RuO2 . The electrode also maintains strong durability during long-term electrolysis process at the fixed current density of 10 mA cm −2 . It is expected that the (NiFe)S2 -GN material can serve as a promising non-noble metal electrocatalyst for OER. Graphical abstract: Image 1